A Survey on Content Injection Attacks - Sandeep D, Sukhdeve; Channe, Hemlata (International Journal of Computer Sciences and Engineering, 2025)
We are increasingly relying on web, and performing important transactions online through it. At the same time, quantity and impact of security vulnerabilities in such applications has grown as well. This work presents a survey of web security research which is the emerging domain that implements various detection prevention techniques for hinder content injection attacks on web applications. This paper provides a classification of the research areas on the content injection attacks. In this paper, we analyze important aspects in content injection attacks. In addition, this paper presents a survey of various security mechanisms adopted by web browsers to defend content injection attacks. The goals of this survey paper are two-fold: i) Serve as a guideline for researchers, who are new to web security and want to contribute to this research area, and ii) Provides further research directions required into content injection attack prevention.